A efetividade do direito fundamental social ao Benefício de Prestação Continuada (BPC) devido às pessoas com deficiência - Freitas, Luiz Gonzaga da Cunha (2014)
Search in this dissertation the discussion on the effectiveness of the BPC award Continued provision Benefit established by law n. 8,742, December 7, 1993 and its subsequent amendments, which regulated the Article 203, V, of the Federal Constitution, against the requirements that the law established for its grant, especially in socio-economic and medical expert testimonyin order to handle the crucial point in that many requests are no longer awarded, through an analysis of the legal bases that are mainly after internalization the legal system of the homeland of the place of the ICF-International Classification of functionality, disability and health. The crux of the question is trying to demonstrate that the BPC, understood as a benefit of amparo to the existential minimum, with the wording of article 6, heading, of the Federal Constitution, qualifies as a fundamental right in guard the dignity of the human person and respect for the principle of social need, highlighted by the applicant disability. In this sense, seeks to demonstrate that the State has not yet been able to give the necessary effectiveness to the BPC and the questions of existential minimum to the poor, despite the long treatment given to the subject in the Federal Constitution. To achieve the desired objectives supporting the work on doctrine, the legal system and jurisprudence, opting for the theoretical and dogmatic methodology. Timely reference to some regulations and instruments used by the Special Federal Civil Court of Sao Paulo, with regard to requirements for the granting of the BPC, showing, the illustrative reports content title, expert medical and socioeconomic, as well as judicial decision to assess how this Court faces the question. Still, to Crown the work, if the justices of our courts, with the goal of demonstrating how walks the jurisprudence homeland in dealing with the question of the existential minimum and in particular the assistance benefit, especially for the trial involving the applications of disabled people